15.0k views
2 votes
(-5,-7) and (3,1)

write equation in point slope form, intercept form, and standard form

User Sanchez
by
6.3k points

1 Answer

5 votes

Answer:

Please check the explanation

Explanation:

Given the points

  • (-5,-7)
  • (3,1)

Determining the slope between the points:


\mathrm{Slope}=(y_2-y_1)/(x_2-x_1)


\left(x_1,\:y_1\right)=\left(-5,\:-7\right),\:\left(x_2,\:y_2\right)=\left(3,\:1\right)


m=(1-\left(-7\right))/(3-\left(-5\right))


m=1

Writing the equation in point-slope form

As the point-slope form of the line equation is defined by


y-y_1=m\left(x-x_1\right)

Putting the point
(-5,-7) and the slope
m = 1 in the line equation


y-y_1=m\left(x-x_1\right)


y-\left(-7\right)=1\left(x-\left(-5\right)\right)\\

Hence, the equation in the point-slope form will be:


y-\left(-7\right)=1\left(x-\left(-5\right)\right)

Writing the equation in slope-intercept form

As the point-slope of the equation is


y=mx+b

where m is the slope and b is the y-intercept

Putting m = 1 and (3, 1) to determine the y-intercept


y = mx+b


1 = 1 (3) + b


1 = 3 + b


b = -2

so putting
b=-2 and m = 1 in the slope-intercept form


y = mx+b


y = (1)x + (-2)

Therefore, the equation in slope-intercept form is:


y = x -2

Writing the equation in the standard form form

As we know that the equation in the standard form is


Ax+By=C

where x and y are variables and A, B and C are constants

As we already know the equation in slope-intercept form


y = (1)x + (-2)

so just simplify the equation to write in standard form


y = (1)x + (-2)


y = x - 2


y - x = -2

User TheKeymaster
by
6.1k points